PELAKSANAAN E-TILANG UNTUK MENCEGAH PRAKTIK PUNGUTAN LIAR DI DAERAH SANGATTA - ONY ROSIFANY; VIKTOR HASIHOLAN HUTAGAOL (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
The increase in traffic violations is a new challenge for the Police to be able to apply sanctions that are educational but still have a deterrent effect. .